Molecular characteristics of non-small cell lung cancer tissue based on quantitative indicators of progesterone receptors expression - I. P. Romanov; T. A. Bogush; A. M. Scherbakov; A. A. Alimov; E. A. Bogush; A. B. Ravcheeva; A. Lee; V. S. Kosorukov (Антибиотики и Химиотерапия, 2024)
Background. Progesterone receptors (PR) are regulators of cell proliferation and therefore can be considered as an aim for targeted medications in the treatment of oncological diseases. At the same time, a quantitative assessment of PR expression in the tissue of non-small cell lung cancer (NSCLC), which has not yet been carried out in other studies, will determine the possibility of using PR modulators for the treatment of this disease and identify the potential category of patients most susceptible to these drugs.Purpose. To characterize NSCLC by quantitative indicators of PR expression and to determine the correlation of clinically significant characteristics of patients and clinical and morphological parameters of a NSCLC tumor with the PR expression to assess the possibility of using PR modulators in the treatment of this disease.Methods. The PR expression in 130 surgical samples of NSCLC was quantified using an immunofluorescence method associated with flow cytometry. Primary antibodies to PR (NBP2-46388) and secondary antibodies conjugated with DyLight650 (ab98729) were used.Results. The expression of progesterone receptors was detected in all the studied tumors; an abnormal distribution of the marker expression level was noted (P=0.01). The mean expression level was 55.3±16.2%, and the median was 57% with a range of 70%, which indicates heterogeneity of PR expression in tumors of different patients. There were no statistically significant differences in the level of PR expression depending on the histotype and stage of NSCLC, as well as on the sex of patients. At the same time, the level of expression and the frequency of overexpression of PR (>67%) in tumors in non-smoking patients are higher than in smokers (P⩽0.02).Conclusion. The high frequency of occurrence and level of PR expression in NSCLC indicate the possible effectiveness of the use of their modulators in the treatment of this disease, especially in non-smoking patients.